Hepatitis B: A Pilot study on awareness and attitude among staff nurses and students of a teaching hospital in India - Ramandeep Singh Gambhir; Ridhi Aggarwal; Aanchal Gupta; Satinder Singh Walia; Nupur Hingad; Garish Kumar (Roczniki Panstwowego Zakladu Higieny, 2024)
Background Hepatitis B is a serious public health concern and health care professionals especially nurses are at higher risk of acquiring this infection. Basic knowledge, awareness and a positive attitude are required to prevent this disease.